Psychological Profile of Students in South Sulawesi: A Study of Self-Forgiveness and Coping Self-Efficacy - Harum, Akhmad; Aswar, Aswar; Maslina, Maslina; Hikmah, Muh. Syawal (IAIN Kudus, 2025)
Psychological Profile of Students in South Sulawesi: A Study of Self-Forgiveness and Coping Self-Efficacy. This reserch aims to describe the self-forgiveness and coping self-efficacy profiles of adolescents in South Sulawesi as a basis for developing guidance services. The local context of South Sulawesi, with its culture of siri’ na pacce (self-esteem and solidarity), sipakatau (mutual humanization), and sipakainge (mutual reminders), has the potential to influence how adolescents forgive themselves and cope with life's pressures. A descriptive quantitative approach was used with 971 students (aged 12–18), consisting of 306 boys and 665 girls. The instruments used were the Heartland Forgiveness Scale (HFS) and the Coping Self-Efficacy Scale (CSES). The results showed that the majority of students were in the moderate category for self-forgiveness (73.56%) and coping self-efficacy (69.55%). These two abilities were relatively equal between boys and girls. Gender equality in this aspect is important to ensure that the counseling program developed is inclusive and responsive to the emotional needs of all student groups. These findings indicate the need for structured counseling programs to optimize students' self-acceptance, emotional management, and adaptive coping strategies.Keywords: Self-Forgiveness; Coping Self-Efficacy; Adolescents; Guidance and Counseling